Arthroscopic release of the elbow joint - Strafun, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
The contracture of the elbow joint is a common complication after the injuries of this anatomical localization. Objective: to evaluate the clinical outcome and changes in range of motions after arthroscopic mobilization surgery on the elbow joint. Methods: f or t he p eriod f rom 2 012 t o 2 018, 1 6 p atients w ith contractions of the elbow joint (5 women (31.25 %) and 11 men (68.75 %) aged 17 to 46 years) have been operated using arthroscopic technique. We examined the patients from 6 months to 76 months after surgery (on average (32.25 ± 24.32) months after surgery). In 8 patients (50 % of all operated) we evaluated the range of motions in the elbow joint, the severity of the pain syndrome on visual analog scale (VAS), and the effectiveness of treatment with the Mayo Elbow Performance Score (MEPS). Results: before the operation flexion in the elbow joint was 106.87° ± 23.44° and the extension was 26.25° ± 15.75°. The average arc of flexion-extension movements before the surgery was 80.62° ± 11.78°. According to the VAS, pain before surgery was (4.75 ± 1.38) points on average. After surgery, flexion in the elbow joint was 131.25º ± 8.34º in average, extension 9.37º ± 10.15º. The average arc of flexion-extension movements after the operation increased to 121.87º ± 17.30º. The average increase of flexionextension movements in the elbow joint was 45º ± 17.52º. Pain according to VAS after surgery was (1.37 ± 1.3) points in average. The results of treatment MEPS were (95.62 ± 6.78) points on average. Thus, we received 6 excellent (75 %) and 2 good (25 %) results of treatment of patients with elbow joint contractions. Conclusions: arthroscopic mobilization of the elbow is a technically complex and effective method of elbow joint contractions treatment, it allows to increase the volume of flexion-extension movements in the elbow joint and obtain excellent and good results of treatment according to MEPS after (32.25 ± 24.32) months after surgery.